PENGARUH MODEL CONTEXTUAL TEACHING AND LEARNING TERHADAP KETERAMPILAN MENULIS DESKRIPSI PESERTA DIDIK SEKOLAH DASAR (PENELITIAN QUASI EKSPERIMEN DI KELAS IV SDN 071 SUKAGALIH) - Rizki Tiara Putri; Dindin MZM; Arifin Ahmad (STKIP Subang, 2023)
This study was motivated by the low writing skills of students. This research is a type of quantitative research with quasi experimental method. The design of this research is nonequivalent control group while the population used is all fourth grade students with samples used as many as 2 classes, namely class IV C as the experimental class and class IV D as the control class. The results showed: 1) The description of the implementation of learning in the experimental class has been well implemented. This can be proven by the average posttest score data of students who have an increase of 82.32 after being taught using the contextual teaching and learning learning model. 2) There is an increase in students' writing skills between students who only use the lecture method and students who use the contextual teaching and learning model. This is evident from the results of the gain test there is an increase of 47% in the experimental class and an increase of 29% in the control class. 3) Based on the results of the effect size test, the use of the contextual teaching and learning model has a moderate effect. Based on the results of the analysis of this study, it can be concluded that the use of contextual teaching and learning model can affect students' description writing skills.